Epi on Safari: A training course report - International Livestock Research Institute (International Livestock Research Institute, 2013)
The "Epi on Safari" training course was held from 24 April to 3 May 2013 at the Serena Mountain Lodge, Mount Kenya National Park, Nyeri. The course was designed for a small group of newly recruited postdoctoral fellows and graduate students attached to the Food Safety and Zoonoses program of the International Livestock Research Institute (ILRI). The main objectives of the course were to: (1) introduce the postdoctoral scientists to epidemiology research at ILRI; (2) identify areas for targeted capacity strengthening through discussion and practical; and (3) get input on epidemiological real world datasets we are working on.